1994
DOI: 10.1002/ajhb.1310060304
|View full text |Cite
|
Sign up to set email alerts
|

Predictive accuracy of bioelectrical impedance equations for women

Abstract: This study assessed the predictive accuracy of age-and fatnessspecific BIA equations in estimating the fat-free mass (FFM) of a heterogeneous sample (N = 152) of women, 20-72 years (yr), with 11-57% body fat (BF). The criterion method was hydrostatic weighing (HW) at residual volume. The Siri (Siri [196ll Natl. Acad. Sci., pp. 7f3-89) two-component model was used to convert body density into relative body fat (% BF) for calculation of criterion FFWHw Average FFM,, and predicted FFM,, did not differ significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…La ecuación de LOHMAN (1992) para mayores (de 50 a 70 años de edad) fue desarrollada utilizando ese modelo (multicomponentes) estimado la MLG, ajustada para el mineral óseo, con un grado aceptable de precisión (EPE = 3,0kg en hombres y 2,8kg en mujeres). La validación cruzada de las ecuaciones para mayores de LOHMAN (1992) en una muestra adicional de mujeres mayores, variando de 50 a 70 años, por JENKINS et al (1994) y WILSON et al (1992 resultó en pequeñas diferencias no signifi cativas en la MLG (< 0,8kg). Ya en el presente estudio, a pesar de una menor diferencia en la MLG (0,6kg), esa fue subestimada de forma signifi cativa, acepción esa quizás devisa al tamaño de la muestra de este estudio (n = 95).…”
Section: Discussionunclassified
“…La ecuación de LOHMAN (1992) para mayores (de 50 a 70 años de edad) fue desarrollada utilizando ese modelo (multicomponentes) estimado la MLG, ajustada para el mineral óseo, con un grado aceptable de precisión (EPE = 3,0kg en hombres y 2,8kg en mujeres). La validación cruzada de las ecuaciones para mayores de LOHMAN (1992) en una muestra adicional de mujeres mayores, variando de 50 a 70 años, por JENKINS et al (1994) y WILSON et al (1992 resultó en pequeñas diferencias no signifi cativas en la MLG (< 0,8kg). Ya en el presente estudio, a pesar de una menor diferencia en la MLG (0,6kg), esa fue subestimada de forma signifi cativa, acepción esa quizás devisa al tamaño de la muestra de este estudio (n = 95).…”
Section: Discussionunclassified
“…In 1988, Segal et al 22 developed and cross-validated fatness-specific equations for women (, 30% BF and $ 30% BF) and men (, 20% BF and $ 20 %BF) ( Table 1). Researchers have reported that the Segal fatnessspecific equations accurately predict two-component model estimates of average FFM in obese, American Indian women, 23 obese, white women, 24 slightly obese men, 25 and obese women and men with less than 42% BF. 26 These equations require the technician to know the individual's %BF beforehand in order to choose the correct fatness-specific equation (nonobese or obese equation).…”
Section: Whole Body Bia Equationsmentioning
confidence: 98%
“…The equation by LOHMAN (1992) for elderly ones (from 50 to 70 years old) was developed using this module (multi components) estimating the MLG, adjusting for the bones mineral, with a grade acceptable of precision (EPE=3.0 kg on men and 2.8 kg on women). The validation crossed on the equations for elderly ones by LOHMAN (1992) in an additional sample on elderly women, varying among 50 and 70 years old, by JENKINS et al, (1994) and WILSON et al, (1992) resulted in a little difference which are not signifi cant on the MLG (<0.8 kg). Now on the present study, due to a less signifi cant difference on the MLG (0.6 kg), this was sub estimated in a signifi cant way this signifi cant may be due to the size of the sample from this study (n=95).…”
Section: Discussionmentioning
confidence: 99%